C++ data type and OOP interactive learning for intermediate students / Mohd Azham Shaari - Shaari, Mohd Azham (2006)
The increasing of importance of speed and interactive learning has been growing rapidly from years to years. C++ Data Type and OOP Interactive Learning was specially design for students that already have basic knowledge C++ programming language. It is a tool to assist students understands more about those topics covered in the class. The system integrates all elements of audio, images and graphics to create the interactivity environments. Researches are made from journals, articles and notes to ensure that the system will be beneficial to students that use it. The system gives a lot of benefits to students as it speed up learning and understanding. Besides, the system also suits for references and guidance